Efficient Ramsey equilibria - Robert A. Becker; Tapan Mitra (Cornell University, Center for Analytical Economics (CAE), 2011)
Ramsey equilibrium models with heterogeneous agents and borrowing constraints are shown to yield efficient equilibrium sequences of aggregate capital and consumption. The proof of this result is based on verifying that equilibrium sequences of prices satisfy the Malinvaud criterion for efficiency.
Keywords: 330